The synthetic cannabinoids phenomenon: from structure to toxicological properties. A review - Alves, Vera L. (2020)
The word “cannabinoid” refers to every chemical substance, regardless of structure or origin, that joins the cannabinoid receptors of the body and brain and that have similar effects to those produced by the Cannabis plant and based on their source of production, cannabinoids can be classified into endocannabinoids, phytocannabinoids and synthetic cannabinoids. Synthetic cannabinoids represent the largest class of drugs detected through the EU Early Warning System with a total of 190 substances notified from 2008 to 2018 and about 280 have been reported worldwide to the United Nations Office on Drugs and Crime. Sprayed on natural herb mixtures with the aim to mimic the euphoria effect of cannabis and sold as “herbal smoking blends” or “herbal incense” under brand names like “Spice” or “K2”, synthetic cannabinoids are available from websites for the combination with herbal materials or more recently, for the use in e-cigarettes. Currently labeled as “not for human consumption” to circum vent legislation, their legal status varies by country with many government institutions currently push ing for their control. However, due to the emergence of new substances, it requires a constant update of the list of controlled drugs. Little is known about how these substances work and their toxic effects in humans and the same product could vary not only in the amount and in the type of substance added. In the last years, synthetic cannabinoids have been associated with deaths and acute intoxica tions in Europe and, despite a range of new measures introduced in this area, continue to represent a challenge to current drug policy models. These synthetic substances are much more potent than nat ural cannabis, as well as displayed greater efficacy, acting as full agonists at the cannabinoid receptors. It is possible that, along with being highly potent, some may also have long half-lives, potentially lead ing to a prolonged psychoactive effect. The present work provides a review on existing literature about the development of synthetic cannabinoids as substances of abuse, current patterns of abuse and their legal status, chemical classification, and some pharmacological and toxicological properties.